Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1080/09581596.2014.953035
|View full text |Cite
|
Sign up to set email alerts
|

Snack food advertising in stores around public schools in Guatemala

Abstract: Obesity in school-age children is emerging as a public heath concern. Food marketing influences preferences and increases children's requests for food. This study sought to describe the type of snack foods advertised to children in stores in and around public schools and assess if there is an association between child-oriented snack food advertising and proximity to schools. All food stores located inside and within a 200 square meter radius from two preschools and two primary schools were surveyed. We assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 44 publications
(30 reference statements)
5
43
0
2
Order By: Relevance
“…These findings are similar to urban Guatemalan schools and described how, in that setting, energy-dense snacks and sugarsweetened beverages available at kiosks around schools comprise a large proportion of the school food environment. [18][19][20]32 Even though out-of-school and working adolescents seem to have less eating habit disruption, they struggled to find time for physical activity and therefore had a much more sedentary lifestyle than their counterparts enrolled in school. They identified home and work responsibilities, significant life changes (e.g., pregnancy) triggering transition out of school, and access to opportunities afforded by the school environment as limiting factors to exercise.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings are similar to urban Guatemalan schools and described how, in that setting, energy-dense snacks and sugarsweetened beverages available at kiosks around schools comprise a large proportion of the school food environment. [18][19][20]32 Even though out-of-school and working adolescents seem to have less eating habit disruption, they struggled to find time for physical activity and therefore had a much more sedentary lifestyle than their counterparts enrolled in school. They identified home and work responsibilities, significant life changes (e.g., pregnancy) triggering transition out of school, and access to opportunities afforded by the school environment as limiting factors to exercise.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, participants not enrolled in school and working purchased processed food less often (50%) 19 Ann. N.Y. Acad.…”
Section: Food Sourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…In Mongolia and the Philippines (Kelly et al, 2015) and in Guatemala (Chacon, Letona, Villamor, & Barnoya, 2015), food advertising, in general, and child-oriented food advertising, in particular, were more frequent in areas nearer to schools. Chacon et al (2015) also found that one-third of all snack food advertisements in stores within short walking distance of schools are child oriented.…”
mentioning
confidence: 97%